2010
DOI: 10.1016/j.jvs.2009.08.057
|View full text |Cite
|
Sign up to set email alerts
|

A case of traumatic internal carotid artery aneurysm secondary to carotid shunting

Abstract: The use of a carotid shunt is a well-accepted method for the prevention of cerebral ischemia during carotid surgery. Although carotid surgeons are familiar with the risks associated with shunt use, few reports have been published detailing the nature, incidence, or severity of shunt-related complications. We report on a patient with dilatation of the distal cervical internal carotid artery at the site of Pruitt-Inahara (LeMaitre Vascular, Inc. Burlington, Mass) shunt balloon inflation. To our knowledge, this c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 11 publications
(11 reference statements)
1
14
0
Order By: Relevance
“…A similar case was described by the Department of Vascular Surgery at the University of Florence. This study concluded with the similar notion that PA formation can be seen with overinflation of the balloon [11]. We cannot be certain of the exact mechanism of how the PA formed, and more studies must be done to identify the complications of shunt induced blunt trauma.…”
Section: Discussionsupporting
confidence: 70%
“…A similar case was described by the Department of Vascular Surgery at the University of Florence. This study concluded with the similar notion that PA formation can be seen with overinflation of the balloon [11]. We cannot be certain of the exact mechanism of how the PA formed, and more studies must be done to identify the complications of shunt induced blunt trauma.…”
Section: Discussionsupporting
confidence: 70%
“…2 PAs of the internal carotid artery distal to the surgically exposed zone are very rare; the main etiology in such cases has been attributed to Pruitt-Inahara shunt balloon inflation. 3,4 This device is commonly used during CEA to provide blood flow to the brain whenever intolerance to vessel clamping occurs. A balloon is inflated in both the common and the internal carotid artery to fix the device during endarterectomy.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 In the first one, 3 the authors reported that, considering the small size of the PA which remained unchanged during follow-up, they decided against taking an invasive approach. They also suggested 3 explanations for PA formation after CEA: distal balloon overinflation, normal balloon inflation in a previously damaged area of the artery, and local dissection followed by PA formation.…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 ] Studies on ECAA mostly comprise case reports or small case series focusing on diagnostic imaging and treatment outcome. [ 2 , 4 6 ] Although the natural course of ECAA is largely unknown, the clinical presentation of ECAA may be accompanied with significant morbidity. Previous studies reported a stroke prevalence of 50% and a mortality of 60–70% when ECAA is left untreated.…”
Section: Introductionmentioning
confidence: 99%